2023
DOI: 10.1021/acs.energyfuels.3c03713
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Assisted Morphology-Induced Nickel Metal–Organic Framework as a Highly Efficient Electrode for Energy Storage Application

S. Siva Shalini,
A. Chandra Bose

Abstract: The rise in need has led to the requirement of advanced smart materials to conquer the present and future disasters in energy storage and generation. Among various materials, metal organic framework (MOF) has been chosen as an active material with tunable structures, porous inorganic− organic structure, and flexibility, which allows it to play a vital role in synthesizing highly efficient energy material. In recent years, MOF materials have voiced remarkable energy storage efficiency and conversion by encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…Nickel is widely distributed in nature and considered as one of the most abundant elements in the Earth’s crust with lower toxicity; hence, Ni-MOFs are considered environmentally friendly materials with sustainable application. Shalini et al had constructed a series of Ni-MOFs by regulating the solvent ratio using a hydrothermal method wherein the prepared N-0.5 MOF electrode material achieved a remarkable specific capacity of 1004.67 C g –1 at a current density of 1 A g –1 . Moreover, a hybrid supercapacitor device was constructed with N-0.5 as the anode and activated carbon (AC) as the cathode, and it was suggested that the developed electrode exhibited superior electrochemical performance, making it a viable supercapacitor electrode option.…”
Section: Research Status Of Mof-based Materials As Supercapacitor Ele...mentioning
confidence: 99%
“…Nickel is widely distributed in nature and considered as one of the most abundant elements in the Earth’s crust with lower toxicity; hence, Ni-MOFs are considered environmentally friendly materials with sustainable application. Shalini et al had constructed a series of Ni-MOFs by regulating the solvent ratio using a hydrothermal method wherein the prepared N-0.5 MOF electrode material achieved a remarkable specific capacity of 1004.67 C g –1 at a current density of 1 A g –1 . Moreover, a hybrid supercapacitor device was constructed with N-0.5 as the anode and activated carbon (AC) as the cathode, and it was suggested that the developed electrode exhibited superior electrochemical performance, making it a viable supercapacitor electrode option.…”
Section: Research Status Of Mof-based Materials As Supercapacitor Ele...mentioning
confidence: 99%